Space-weighted seismic attenuation multi-frequency tomography at Deception Island volcano (Antartica) - Guardo, Roberto Antonino (2020)
Fil: Guardo, Roberto Antonino. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.